CRUSTAL VELOCITY MODELS OF SHEAR WAVES IN EAST ANTARCTICA BY RECEIVER FUNCTION INVERSION OF BROADBAND WAVEFORMS - カナオ, マサキ; クボ, アツキ; シブタニ, タクオ; KANAO, Masaki; KUBO, Atsuki; SHIBUTANI, Takuo (National Institute of Polar Research, 1996)
P(論文) Receiver functions from teleseismic earthquakes recorded with broadband seismographs at Dumont d'Urville Station (66.7°S, 140.0°E; DRV) and Mawson Station (67.6°S, 62.9°E; MAW), East Antarctica, are inverted for shear wave velocity models of the crust and uppermost mantle beneath the recording stations. The obtained models are compared with the previously obtained ones of Syowa Station (69.0°S, 39.6°E; SYO) to clarify the relationship with regional tectonic history. A crustal velocity model around DRV derived from 18 events indicates a rather sharp Moho at a depth of 38km and somewhat less fluctuation within the crust. It might have originated in the Early Proterozoic metamorphism in Adelie Land. High velocity zones in the upper crust together with low velocity discontinuity of the mid-crust may also have a relation to past tectono-thermal activity. A crustal velocity model around MAW determined by using 20 events has a very sharp Moho at 42km depth that might have developed under high pressure and a thickened crust when a metamorphic event occurred around Mac. Robertson Land in the Late Proterozoic ages. Variation in the crustal velocities at MAW is intermediate among the three stations, which may also have been created by the regional metamorphism. departmental bulletin paper